PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PNDEKATAN THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII6 SMP NEGERI 4 SIAK HULU Rosi Nurkotimah1, - Nurkotimah, Rosi; Zulkarnain, Zulkarnain; Zuhri D, Zuhri D (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is classroom action research that aims to improve learning process and to increase mathematics achievement with applied the learning cooperative approach Think Pair Square (TPS) model. The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection.The subject of this research is student of class VIII6 SMPN 4 Siak Hulu in academic years 2017/2018, which amounted to 40 students, consist of 19 boys and 21 girls. The instruments of data collection in this research were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the students’ Mathematic tests were analyzed in quantitative descriptive. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycle. Most of students were very confidenced and actived in learning process, such as while they were finished mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning. Number of students that reach Minimum Mastery Criteria increase from basic score to first test I and II. The results of this research showed an increasing number of students learning mathematicsabout knowledge of the basic score (42,5%)to the first test (62,5%) to the second test II (80%). For the skills of basic score the first test (72,5%) to the second test (95%), Results of this research indicates that appication of the learning cooperative approach Think Pair Square (TPS) model can improve learning process and increase mathematics achievement from the students at class VIII6 SMPN 4 Siak Hulu in academic years 2017/2018 for the subject matter relations and functions.Key Words: Mathematics Achievement, Learning Cooprative Approach ThinkPair Square (TPS)